The Impact of the 2023 Türkiye Earthquakes on Glycemic Control and Stress Levels in Children with Type 1 Diabetes: Single-center Experience - Gül Trabzon; Seda Aybüke Sarı; Servet Yüce; Simge Bilaloğlu; Şeyma Demiray Güllü (JCRPE)
Objective: The 2023 earthquakes in southeastern Türkiye significantly impacted physical and emotional well-being in the region. This study evaluated the effect of the earthquakes on glycemic control, diabetes management, and stress levels in children with type 1 diabetes mellitus (T1DM). Methods: Pediatric T1DM patients were assessed before and after the earthquake. Key parameters included glycated hemoglobin (HbA1c), insulin dosage, and psychological assessments using the Problem Areas in Diabetes Scale-Teen (PAID-T) version and the Post-Traumatic Stress Reaction Scale (PTSRS). Mixed-effects models were used to compare data across time points. Results: Of the 79 participants, 45.6% were male, with a mean age of 143.5±45.0 months. The earthquake disrupted insulin therapy in 36.7% of patients and caused glycemic control issues in 77.2%. HbA1c levels dropped from 9.7±2.7% pre-earthquake to 8.8±2.2% in the first three months, rose to 10.6±1.9% in the following three months, and stabilized at 9.7±1.9% by the fourth period. A positive correlation was observed between parental stress and children’s HbA1c (r=0.423, p=0.031). Psychological effects were notable, with 43% reporting distress, and 63.3% experiencing loss of close family or friends. The mean PAID-T scores were 42.0±14.5 for children and 53.7±12.8 for parents, indicating a moderate to high level of diabetes-related distress in both groups. Although no validated cut-off score exists for the PAID-T, higher values reflect a greater perceived burden. The mean PTSRS score was 35.1±17.4, which corresponds to a moderate level of post-traumatic stress reaction based on established cut-off values 35.1±17.4. Conclusion: The earthquake significantly affected glycemic control and psychological well-being in children with T1DM. Fluctuations in HbA1c levels and the link between parental stress and glycemic outcomes suggest a need for tailored interventions during crises.